Human-Animal Relationship and the Ethics of Using Animals in Islam - Dahlan-Taylor, Magfirah (Concilium, 2022)
This essay discusses arguments for and against the permissibility of using animals in Islam. Qur'anic passages understood as evidence of the right to use animals in Islam are often interpreted in a similar manner to those found in the Bible; namely in terms of dominion of humans over nonhuman animals. But the same passages can be read differently, in a way that interprets human-animal relationship in terms of vulnerable dependency rather than hierarchical superiority. This essay discusses the ethical implications of interpreting the Qur'anic passages that speak to human-animal relationship in terms of vulnerable dependency.